Book covers: Past & present / Caroline Joseph ...[et al.] - Joseph, Caroline; Mat Pardi, Khalid; Aminullah, Rosita; Bakar, Sulaila (2013)
'Don't judge a book by its cover' is rather a common expression that relates to the fact that a not so pretty cover of a book is no yardstick to an interesting novel. However, lime and age have changed this perception. Marketing strategies and promotion, associated to the business line, have managed to penetrate and further influence the world of publication into selling books that is proven a competitive business today. Thus, books nowadays tend to be dressed with glossy and pretty covers in order to display attractive pieces on bookshelves. In line with this, this study is aimed at comparing the covers of English language books from various publications with same titles but published at different ages; the past and the present.